2010
DOI: 10.1002/rcm.4753
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced metabolite identification with MSE and a semi-automated software for structural elucidation

Abstract: The identification of metabolites is almost exclusively done with liquid chromatography/tandem mass spectrometry (LC/MSMS) and despite the enormous progress in the development of these techniques and software for handling of data this is a time-consuming task. In this study the use of quadrupole time-of-flight (QTOF)-generated MS(E) and MS/MS data were compared with respect to rationalization of metabolites. In addition Mass-MetaSite, a semi-automated software for metabolite identification, was evaluated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 21 publications
0
71
0
Order By: Relevance
“…To the best of our knowledge, this work represents the fastest ever utilization of MS E . In 2010, Bonn et al reported LC-MS E of metabolites with a summed scan time of 100 ms. 29 In this manuscript, the summed scan speed was 50 ms, sampling twice as fast. Figure S2 in Supporting Information shows representative peaks from both the microchip CE-ESI electropherogram and the LC-MS chromatogram, illustrating the number of MS data points across each peak.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, this work represents the fastest ever utilization of MS E . In 2010, Bonn et al reported LC-MS E of metabolites with a summed scan time of 100 ms. 29 In this manuscript, the summed scan speed was 50 ms, sampling twice as fast. Figure S2 in Supporting Information shows representative peaks from both the microchip CE-ESI electropherogram and the LC-MS chromatogram, illustrating the number of MS data points across each peak.…”
Section: Resultsmentioning
confidence: 99%
“…A number of methods have been developed that annotate m/z values in a fragmentation spectrum with in silico generated substructures of possible candidate molecules. Methods based on the concept include EPIC [ 22 ] (available as MassFragment software from Waters), Mass-Frontier [ 23 ], FiD [ 24 ], MetFrag [ 25 ] and MassMetaSite [ 26 ]. We recently described an extended algorithm that can handle multistage spectral trees, obtained from LC-MSn experiments, where n > 2 [ 27 ].…”
Section: Automated Structure Elucidationmentioning
confidence: 99%
“…Subsequently, the energy is increased till reasonable comprehensive fragmentation profile is obtained. A few modern mass spectrometers have the facility of collision energy ramping, along with auto polarity switching, which can be exploited to gain maximum information in a single LC-MS run [143,144]. An important aspect that may need attention at this stage is that during MS runs using atmospheric pressure ionization sources, one usually encounters peaks for adducts of molecular ions with sodium (+22 Da), potassium (+38 Da) and/or ammonium (+17 Da) ions in positive ionization mode, and those due to chloride (+36 Da), acetate (+60 Da) and formate (+46 Da) in the negative mode.…”
Section: Sample Preparationmentioning
confidence: 99%